The long game: Telemedicine patient satisfaction metrics and methods of recurrence detection for gynecologic cancer patients throughout the initial year of the COVID-19 pandemic - Rachel P. Mojdehbakhsh; Arielle C. Mora Hurtado; Shitanshu Uppal; Hailey Milakovich; Ryan J. Spencer (Elsevier, 2022)
Objective: The primary aim of this study was to evaluate gynecologic cancer patients' satisfaction with telemedicine visits over a one-year period during the COVID-19 pandemic. The secondary aim was to characterize how gynecologic cancer recurrence was detected with high telemedicine utilization. Methods: A survey study and a retrospective cohort study of patients participating in telemedicine visits between April 20, 2020 and March 30, 2021 in a gynecologic oncology clinic were undertaken. To assess patient satisfaction with telemedicine visits, the Telemedicine Satisfaction Survey (TeSS) was administered to patients by phone. Retrospective chart review was conducted to gather clinical data regarding diagnosis, treatment, and recurrence. Results: Three hundred and sixteen patients completed the TeSS for a response rate of 80.2%. Patients rated the following aspects of the telemedicine encounter as good or excellent: quality of technology (97.8%), personal comfort (90.8%), length-of-visit (95.2%), treatment explanation (93.7%), overall experience (92.7%). Moreover, 87.0% of patients would use telemedicine again. Retrospective data was collected for 394 patients, 312 of which had invasive cancer (79.2%). Twenty-nine (7.4%) patients experienced a recurrence during the study period. The most common method of detection was patient-reported symptoms (n = 17, 58.6%). The remaining recurrences were diagnosed by scheduled biomarkers (n = 7, 24.1%), scheduled imaging (n = 4, 13.8%) and asymptomatic exam (n = 1, 3.4%). Conclusions: After one year of the COVID-19 pandemic and the implementation of routine telehealth visits, gynecologic cancer patients were overwhelmingly satisfied with the use of telemedicine. During this period, recurrences were most often diagnosed by patient-reported symptoms.